Edukasi Kebersihan Lingkungan Sekolah sebagai Upaya Pembentukan Karakter Peduli pada Peserta Didik MDTA Nurul Huda Desa Padamaju - Samsu Nurfalah; Eva Manfaatin; Talina Talina; Nurul Hawani Rahayu Putri; Santi Sri Melani; Muhammad Raihan Nawawi (Lembaga Pengembangan Kinerja Dosen, 2025)
School cleanliness is a fundamental aspect in creating a healthy, comfortable, and character-based learning environment. This community service activity aims to raise students’ awareness of the importance of maintaining school environmental hygiene through a Participatory Action Research (PAR) approach conducted at MDTA Nurul Huda, Padamaju Village, Pagelaran District, Cianjur Regency. The activity consisted of several stages: observation, educational counseling, collaborative cleaning activities, and participatory evaluation. The results show an increased awareness among students of the importance of cleanliness, a more organized school environment, and active involvement of teachers and students in maintaining school facilities. Teachers served as role models who significantly influenced students’ clean habits. The activity also affirmed the integration of Islamic values in hygiene education, aligning with the principle of an-nadhafah minal iman (cleanliness is part of faith). Therefore, the school cleanliness education program at MDTA Nurul Huda is not merely a physical cleaning action but also a sustainable form of character education based on spiritual and social values.